SENSE: a comparison of photon detection efficiency and optical crosstalk of various SiPM devices - Nagai, Andrii; Schultz-Coulon, Hans-Christian; Shen, Wei (Nuclear instruments & methods in physics research. Section A, Accelerators, spectrometers, detectors and associated equipment, 2018)
This paper describes a comparison of photon detection efficiency and optical crosstalk measurements performed by three partners: Geneva University, Catania Observatory and Nagoya University. The measurements were compared for three different SiPM devices with different active areas: from 9mm2 up to 93.6mm2 produced by Hamamatsu. The objective of this work is to establish the measurements and analysis procedures for calculating the main SiPM parameters and their precision. This work was done in the scope of SENSE project which aims to build roadmap for the last developments in field of sensors for low light level detection.